Plasma-enhanced atomic layer deposition of gallium nitride thin films on fluorine-doped tin oxide glass substrate for future photovoltaic application. Issue 5 (1st April 2020) - Qiu, Peng; Wei, Huiyun; An, Yunlai; Wu, Qixin; Du, Wenxin; Jiang, Zengxuan; Zhou, Lang; Gao, Chuang; Liu, Sanjie; He, Yingfeng; Song, Yimeng; Peng, Mingzeng; et al.
Abstract: To serve as an electron transport layer (ETL) or a buffer layer for the third-generation solar cells, a compact and uniform gallium nitride (GaN) thin layer with suitable energy level is needed. Meanwhile, it is also meaningful to explore its low-temperature deposition especially on transparent electrodes. In this work, GaN thin films have been deposited on fluorine-doped tin oxide (FTO) glass substrate for the first time by plasma-enhanced atomic layer deposition (PEALD) technology. 280–300 °C is identified as the optimized deposition temperature for forming a compact and uniform n-type GaN layer on FTO substrate. The 50–200 PEALD cycles of GaN layers show an amorphous structure, and their bandgap values ranging from 3.95 eV to 3.58 eV have been displayed. Interestingly, as the GaN thickness increases, Fermi level moves upward obviously along with a reduction of conduction band minimum (CBM) value as well as an increase of valence band maximum (VBM) value. The thickness-dependent band structure is preliminarily explained as the relaxation of compressive stress and increased carrier concentration for a thicker GaN layer. The above situation enables us to regulate the energy level of GaN layer via thickness control, and thus accelerates its future application in new generation solar cells.